Effects of compliance on trunk and hip integrative neuromuscular training on hip abductor strength in female athletes - Sugimoto, D.; Myer, G. D.; Bush, H. M.; Hewett, T. E. (The Journal of Strength and Conditioning Research, 2014)
Recent studies demonstrate the link between reduced hip abductor strength and increased risk for knee injury such as patellofemoral pain syndrome in women athletes. Meta-analytic reports indicate that the efficacy of integrative neuromuscular training (INT) is associated with compliance to the prescribed programming. Thus, the purpose was to investigate the compliance effects of a trunk and hip-focused INT exercises on hip abductor strength in young women athletes. In a controlled laboratory study design, 21 high school women volleyball players (mean age = 15.6 ± 1.4 years, weight = 64.0 ± 7.4 kg, height = 171.5 ± 7.0 cm) completed isokinetic hip abductor strength testing in pre- and postintervention, which consisted of 5 phases of supervised progressive trunk and hip-focused INT exercises twice a week for 10 weeks. The compliance effects were analyzed based on the changed hip abductor strength values between pre- and postintervention and 3 different compliance groups using 1-way analysis of variance and Pearson's correlation coefficients. The participants in the high-compliance group demonstrated significant hip abductor peak torque increases compared with noncompliance group (p = 0.02), but not between moderate-compliance and noncompliance groups (p = 0.27). The moderate correlation coefficient value (r = 0.56) was recorded between the isokinetic hip abductor peak torque changes and the 3 compliance groups. Because of the observed significant effects and moderate linear association, the effectiveness of a trunk and hip-focused INT protocol to improve hip abduction strength seems dependent on compliance. Compliance of trunk and hip-focused INT is an important aspect of increasing hip abductor strength increase in young women athletes.